UTILIZATION OF ICT LIBRARY SERVICES IN THE FIELD OF LIFE SCIENCES IN THE SELECTED UNIVERSITY LIBRARIES OF UT OF JAMMU AND KASHMIR - Sharma, Amit; Dhar, Meghna (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
The Life Sciences are helpful in improving the quality and standard of life. They have the applications in agriculture, health, medicine, pharmaceuticals and food science industries. The proposed research study attempts to understand the perception of users towards application of Information Communication Technologies (ICT) in the field of Life Sciences of various University libraries of UT of Jammu and Kashmir. Information Communication Technologies have changed the traditional methods of library activities and services providing new dimensions for teaching, learning and research in higher educational institutions. The main objectives of the present study were to find out the usage and frequency of ICT based library services by the library users. It further states their source of training for using ICT based library services and the most preferred mode of communication for use of the ICT based digital library services for research, study or teaching. For study closed and open-ended questionnaire was framed to seek quantifiable information and opinion of users on ICT based information sources and services. About 525 questionnaires were distributed to the users of various universities under study. Of these 490 questionnaires were received back duly filled thereby making the response rate of 93.33%.The data so collected was analyzed and tabulated with the help of various mathematical and statistical techniques .With the help of ICT tools, it is possible to store, retrieve, disseminate and organize information by creating websites and databases. Information is now published both electronically and printed format thereby making it accessible to users according to their demands. This study is helpful in reorienting information and communication technologies, library services and activities to synchronize them with information seeking behaviour of their user’s i.e. teachers, scientists, researchers and students.